2009
DOI: 10.1002/mds.22593
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism in Gaucher's disease type 1: Ten new cases and a review of the literature

Abstract: Parkinsonism has been described in patients with Gaucher's disease (GD). We reviewed the 10 cases of patients with both parkinsonism and GD recorded in the French national GD registry, as well as 49 previously published cases. Relative to the general population, parkinsonism in GD patients (1) was more frequent, (2) occurred at an earlier age, (3) responded less well to levodopa, and (4) was more frequently associated with signs of cortical dysfunction. Enzyme replacement therapy (ERT) and substrate reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
2
18
0
2
Order By: Relevance
“…These patients may benefit from dopamine therapies used for PD whereas enzyme replacement and substrate reduction therapy are ineffective on GD-associated parkinsonism 60. Further, optical coherence tomography (OCT) demonstrated thinning of the retinal ganglion cell layer in GD patients (Type-I) and carriers who manifested clinical markers of early neurodegeneration (cognitive impairment and hyposmia) 14.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may benefit from dopamine therapies used for PD whereas enzyme replacement and substrate reduction therapy are ineffective on GD-associated parkinsonism 60. Further, optical coherence tomography (OCT) demonstrated thinning of the retinal ganglion cell layer in GD patients (Type-I) and carriers who manifested clinical markers of early neurodegeneration (cognitive impairment and hyposmia) 14.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 C]-CFT PET has demonstrated decreased uptake suggestive of presynaptic dopaminergic dysfunction in GBA heterozygotes and homozygotes with parkinsonism, 54, 55 but normal uptake in asymptomatic GBA carriers 54 . F-fluorodopa PET, which evaluates presynaptic dopamine terminals, has demonstrated reduced f-dopa uptake in the striatum of GD1 patients 4, 56 and GBA-PD heterozygotes 52 , similar to IPD. Fluorodeoxyglucose (FDG) PET has shown hypermetabolism in the lentiform nuclei in GD1-PD patients, similar to IPD 4 .…”
Section: Neuroimaging In Gba-pdmentioning
confidence: 97%
“…However, neurological symptoms including peripheral neuropathy and Parkinsonism have increasingly been reported in systematic studies of patientswithGD1 [610]. Additionally, several case reports of patientswithGD1 developing Parkinsonism have been published [1117]. Other studies in patients with known Parkinson's disease demonstrated an association with mutations in the GBA gene [15,1822].…”
Section: Introductionmentioning
confidence: 99%